Faktor-faktor yang mempengaruhi ketepatan waktu pelaporan keuangan - Nurmiati Nurmiati (Faculty of Economics and Business Mulawarman University, 2016)
The financial statements are the financial information presented and delivered by a company to internal and external parties , which includes all business activities of an entity which is one of accountability and communication management tools to the parties that need . The financial statements are the primary means of communicating financial information to parties outside the company . In companies that have gone public they are required to report their financial statements to the public , is governed by Law no.8 of 1995 on capital markets . This study aims to provide empirical evidence about the factors that affect the timeliness of financial reporting, namely; Company size (SIZE), ownership structure (OWN), Provitabilitas, Leverage and Liquidity. Samples were selected by using purposive sampling , which means that the sample used in this study are samples that meet certain criteria . Intended use of this method is to obtain a representative sample . Then the samples used in this study are 240 manufacturing companies that report financial statements in 2008, 2009 and 2010. The results of this study found empirical evidence that firm size (SIZE) positive effect with variable probability of 0.008 , a positive leverage effect with a variable probability of 0,003 and a positive effect on liquidity. While the ownership structure (OWN) no positive effect with the probability of 0.936 and profitability varaibel no positive effect with a variable probability of 0.676 . Keyword: Company size (SIZE) , ownership structure (OWN), Profitability, Leverage, Liquidity